K-State Libraries Usability Team Report - Duever, Meagan; Nash, Marc; Coleman, Jason; Coleman, Tara L.; Littrell, Laurel; Singh, Harleen (Kansas State University. Libraries, 2013)
This usability test was a study of library and institution-specific terminology used on K-State Libraries’ website. It tests whether library patrons understand the terminology and prefer the terminology used when presented. This test was done in the form of a survey. K-State students, faculty, and staff voluntarily answered questions that tested their understanding of selected terminology used on the K-State Libraries' website along with a set of questions that allow respondents to select the best term correlating to a description of services provided by K-State Libraries.
Keywords: Web design; Usability; Terminology; Libraries; Online resources